ANALISIS MINAT DAN FAKTOR YANG MEMPENGARUHINYA MELANJUTKAN STUDI KE PROGRAM PENDIDIKAN PROFESI GURU PADA MAHASISWA PENDIDIKAN EKONOMI PIPS FKIP UNIVERSITAS RIAU - Filza Ahlina; Almasdi Syahza; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to analyze the interests and factors that influence him to continue his studies to the PPG program on students of PIPS FKIP Economic Education Riau University. This research includes quantitative research. The number of samples used in this study was 103 students. The types of data used in this study are primary data. The method of data collection uses questionnaires. The data analysis technique in this study is multiple linear regression analysis. The results showed that there was a positive and significant influence between learning achievement, motivation to become a teacher, parental education and parental income to the interest of continuing to study to PPG program on students of economic education PIPS FKIP Riau University.Key Words: Interests of PPG, Learning Achievements, and Motivation to Become a Teacher